Queenie Malone's Paradise Hotel [large type] - Hogan, Ruth, 1961- (Thorndike press large print basic, 2020)
"Tilly was a bright, outgoing little girl who loved fizzy drinks, naughty words, and liked playing with ghosts and matches. When her beloved father suddenly disappeared, she and her fragile, difficult mother moved into Queenie Malone's magnificent Paradise Hotel in Brighton, with its endearing and loving family of misfits--including the exuberant and compassionate Queenie herself. But then Tilly was dealt another shattering blow when her mother sent her off to boarding school with little explanation and no warning, and she lost her beloved chosen family. Now an adult, Tilda has grown into an independent woman still damaged by her mother's unaccountable cruelty. Wary of people, her only true friend is her dog, Eli. When her estranged mother dies, Tilda returns to Brighton and the home she loved best. With the help of the still-dazzling Queenie, she sets about unraveling the mystery of her exile from The Paradise Hotel, only to discover that her mother was not the woman she thought she knew at all...and that it's never too late to write your own happy ending. With Ruth Hogan's trademark quirky, clever, and life-affirming characters, Queenie Malone's Paradise Hotel will dazzle readers and mesmerize them until they reach the surprising twist at the end"--